Reasons for assisting with injection initiation: Results from a large survey of people who inject drugs in Los Angeles and San Francisco, California. (1st April 2020) - Simpson, Kelsey A.; Kral, Alex H.; Goldshear, Jesse L.; Wenger, Lynn; Strike, Carol S.; Bluthenthal, Ricky N.
Highlights: People who inject drugs (PWID) report a range of different motivations for injection initiation. The relationship between initiation motivations and demographic, economic, and health-related variables was examined. Initiation to prevent injury was associated with being female. Initiation due to pestering was related to recycling income and sex work. Initiation due to skills was associated with age and HIV status, and initiation in exchange for material purposes was related to age, race, education, SSI income, being gay, lesbian, or bisexual, and substance use treatment history. Abstract: Injection drug initiation usually requires assistance by someone who already injects drugs. To develop interventions that prevent people from starting to inject drugs, it is imperative to understand why people who inject drugs (PWID) assist with injection initiation. Methods: Injection initiation history and motives for initiating others were collected from 978 PWID in Los Angeles and San Francisco, CA, from 2016-17. This article documents motivations for providing injection initiation assistance and examines demographic, economic, and health-related factors associated with these motivations using multivariable logistic regression modeling. Results: Among the 405 PWID who ever facilitated injection initiation, motivations for initiating were: injury prevention (66%), skilled at injecting others (65%), to avoid being pestered (41%), in exchange for drugs/money (45%), and for food/shelter/transportation (15%). High frequency initiation (>5 lifetime injection initiations) was associated with all motivations except for being pestered. Initiation to prevent injury was associated with being female. Initiation due to pestering was associated with recycling income and sex work. Being skilled was associated with age and HIV status, while initiation for money or drugs was associated with age, race, education, social security income, and substance use treatment. Lastly, initiation for food, shelter, or transportation was associated with age, sexual orientation and education level. Conclusion: Diverse factors were associated with reported motivations for assisting someone to initiate injection for the first time. Our analysis underscores the need for prevention strategies focused on improving economic and housing conditions along with implementing drug consumption rooms to disrupt the social processes of injection initiation.